Pengaruh Lingkungan Sekolah Terhadap Prestasi Akademik Peserta Didik di SDN 02 Jambak (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to investigate the influence of school environment on the academic achievement of students at SDN 02 Jambak. A quantitative research method using multiple linear regression was employed to analyze the relationship between school environment variables (school facilities, school climate, and teacher support) and academic achievement (exam scores). The results show a significant influence of the school environment on the academic achievement of students at SDN 02 Jambak. School facilities and teacher support variables contributed the most to academic achievement. These findings highlight the importance of improving the quality of school facilities and teacher support to enhance student academic performance. Further research is recommended to consider other variables that may influence academic achievement, such as family and individual factors.